2017
DOI: 10.1016/j.freeradbiomed.2017.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium complex exerts antineoplastic effects that are mediated by oxidative stress without inducing toxicity in Walker-256 tumor-bearing rats

Abstract: The present study evaluated the in vivo antitumor effects and toxicity of a new Ru(II) compound, cis-(Ru[phen][ImH]) (also called RuphenImH [RuC]), against Walker-256 carcinosarcoma in rats. After subcutaneous inoculation of Walker-256 cells in the right pelvic limb, male Wistar rats received 5 or 10mgkg RuC orally or intraperitoneally (i.p.) every 3 days for 13 days. A positive control group (2mgkg cisplatin) and negative control group (vehicle) were also used. Tumor progression was checked daily. After treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
3
13
0
Order By: Relevance
“…Cisplatin, cis -diamminedichloroplatinum (II), is a widely used anticancer drug and is effective against several types of cancers in almost all parts of the body, including cancers of the breast, lung, ovary, testis, head, and neck. Cisplatin was first identified as an inhibitor of cell cycle in 1965 and in due course of time its therapeutic efficacy has been studied widely ( Sadhukhan et al, 2016 ; Alves de Souza et al, 2017 ). Despite its chemotherapeutic activity, different studies reported the toxicity of this molecule in several vital organs of the human body including heart, liver, brain, spleen, and with the most significant deleterious effect in renal tissues ( Fatima et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cisplatin, cis -diamminedichloroplatinum (II), is a widely used anticancer drug and is effective against several types of cancers in almost all parts of the body, including cancers of the breast, lung, ovary, testis, head, and neck. Cisplatin was first identified as an inhibitor of cell cycle in 1965 and in due course of time its therapeutic efficacy has been studied widely ( Sadhukhan et al, 2016 ; Alves de Souza et al, 2017 ). Despite its chemotherapeutic activity, different studies reported the toxicity of this molecule in several vital organs of the human body including heart, liver, brain, spleen, and with the most significant deleterious effect in renal tissues ( Fatima et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the antitumor activity of ruthenium complexes has led to gratifying achievements and the identification of some promising antitumor compounds ( Chen et al, 2016 ; Alves de Souza et al, 2017 ; Zeng et al, 2017b ; Zhao et al, 2018 ). The ruthenium complex showed more potent activities than platinum drugs, and has a significant inhibitory effect on platinum-resistant tumor ( Zeng et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that both complexes exhibit higher cytotoxicity in four cancer cell lines than in normal cells, suggesting that these complexes have high selectivity between tumor cells and normal cells [ 63 ]. Another important in vivo study established that the highest intraperitoneal dose (10 mg/kg) of ruthenium-II complex, cis -(Ru[phen] 2 [ImH] 2 ) 2+ significantly reduced tumor volume and weight, induced oxidative stress in tumor tissue, reduced the respiration of tumor cells, and induced necrosis without inducing apoptosis in the tumor [ 64 ]. More importantly, there was no clinical signs of toxicity or death in tumor-bearing or healthy rats that were treated with cis -(Ru[phen] 2 [ImH] 2 ) 2+ [ 64 ].…”
Section: Safety and Toxicity Of Ruthenium Compounds In Plateletsmentioning
confidence: 99%
“…Another important in vivo study established that the highest intraperitoneal dose (10 mg/kg) of ruthenium-II complex, cis -(Ru[phen] 2 [ImH] 2 ) 2+ significantly reduced tumor volume and weight, induced oxidative stress in tumor tissue, reduced the respiration of tumor cells, and induced necrosis without inducing apoptosis in the tumor [ 64 ]. More importantly, there was no clinical signs of toxicity or death in tumor-bearing or healthy rats that were treated with cis -(Ru[phen] 2 [ImH] 2 ) 2+ [ 64 ]. These results suggested that cis -(Ru[phen] 2 [ImH] 2 ) 2+ has antitumor activity through the modulation of oxidative stress and impairment of oxidative phosphorylation, thus promoting cancer cell death without causing systemic toxicity.…”
Section: Safety and Toxicity Of Ruthenium Compounds In Plateletsmentioning
confidence: 99%